Autoreactive Peripheral Blood T Helper Cell Responses in Bullous Pemphigoid and Elderly Patients With Pruritic Disorders - Didona, Dario; Scarsella, Luca; Fehresti, Milad; Solimani, Farzan; Juratli, Hazem A.; Göbel, Manuel; Mühlenbein, Stefan; Holiangu, Lily; Pieper, Josquin; Korff, Vera; Schmidt, Thomas; Sitaru, Cassian; et al. (Frontiers in Immunology, 2021)
Chronic pruritus is increasingly common in the elderly population and is associated with a variety of dermatoses. Clinical and experimental evidence suggests that pruritus of the elderly may be linked to autoimmunity with loss of self-tolerance against cutaneous autoantigens. Bullous pemphigoid (BP) is a prototypic autoimmune disorder of the elderly, characterized by serum IgG autoantibodies, namely anti-BP180 and anti-BP230, directed against components of the basal membrane zone that lead to sub-epidermal loss of adhesion. Pruritus may be considered as a pre-clinical stage of BP, since a subset of these patients shows serum IgG autoantibodies against BP230 and/or BP180. Thus, the objective of this study was to determine autoreactive T cell responses against BP180 in elderly patients in comparison to patients with BP. A total of 22 elderly patients with pruritic disorders, 34 patients with bullous or non-bullous BP and 34 age-matched healthy controls were included in this study. The level of anti-BP180 and anti-BP230 IgG serum autoantibodies, Bullous Pemphigoid Disease Area Index (BPDAI), and pruritus severity were assessed for all patients and controls. For characterization of the autoreactive T cell response, peripheral blood mononuclear cells were stimulated ex vivo with recombinant BP180 proteins (NH2- and COOH-terminal domains) and the frequencies of BP180-specific T cells producing interferon-γ, interleukin (IL)-5 or IL 17 were subsequently determined by ELISpot assay. Here, we show presence of autoreactive Th1 cells in a minor subset of elderly patients with pruritic disorders, while patients with BP showed a mixed Th1/Th2 response against BP180. Furthermore, our T cell characterization revealed that therapeutic application of topical clobetasol propionate ointment in BP patients significantly reduced peripheral blood BP180-specific T cells, along with clinical symptoms such as pruritus suggesting that autoreactive T cells may be involved in pruritus development.